The Association Between Consanguinity and Offspring with Congenital Hearing Loss in The Eastern Region, Saudi Arabia - Abdullah M. AlKhudair (Wolters Kluwer Medknow Publications, 2024)
Background: Consanguineous marriage is a common practice in the Middle East and in Saudi Arabia especially. Not many studies were done on the relationship between consanguinity and congenital hearing loss (HL) in Saudi Arabia and none in the Eastern Region specifically. Therefore, this study focuses on the determination of the association between consanguinity and congenital HL (CHL). Materials and Methods: This is a comparative cross-sectional study that included any eastern region resident with severe-to-profound CHL. The data were collected and recorded on a structured questionnaire that was distributed among six schools in hard copy. In addition, data were also collected directly from two rehabilitation centers and from the Saudi Association for Hearing Impairment in Dammam. Results: Among 275 participants, the degree of HL was observed to be severe in 92 (33.5%) and profound in 183 (66.5%) participants. Consanguinity was reported to be as high as 75.6%. Most consanguineous marriages were of the first degree, which was found to have an association with higher numbers of severe and profound HL. It was observed that a total of 142 (51.7%) of the participants had at least one or more family members with HL, and 130 (47.3%) had at least one or more relatives with HL. Furthermore, it was found that those who reported blood-related parents had higher percentages of family members/relatives with the same condition. Conclusion: The outcome of this study is suggestive that there is an association between consanguineous marriage and having children with CHL. Looking at these findings and how consanguineous marriage is still commonly practiced, it is crucial to spread awareness regarding the dangers and possible associated disorders affecting children when marrying relatives.